The use of LMS Moodle and Moodle Mobile App in educational process at the Faculty of Medicine in Hradec Králové - Kordek, David; Kopeček, Martin (Mefanet journal, 2019)
In the initial part of the contribution the reader is made familiar with the main aim of the project, the individual phases of the project and planned outputs of the project. In the second part of the contribution there is a description of the possibilities of e - learning in general and at the Faculty of Medicine in Hradec Kralove, where the program LMS Moodle has been used for e-learning for 8 years. With regards to the project timetable it ́s possible to present to the reader the results of the questionnaire and the elaborated electronic courses. In the part about methods and materials the readers get to know the Moodle Mobile App, there is a description of its possibilities of use when working with the courses and it takes into account the experience of the authors at our faculty. The conclusion of the contribution thus concludes the possibilities of use of the Moodle Mobile App and is different from the project that is in its first phase.
Keywords: mobilní aplikace; studium lékařství; audiovizuální pomůcky; Mobile Applications; Education, Medical; Audiovisual Aids; učební pomůcky; Teaching Materials